Metodologi Ulumul Qur'an dalam Menghadapi Tantangan Tafsir Modern - Muhammad Parhun; Dwi Januarti; Dinda Firda; Bahrul Zikri; Adelia Putri Cahyani (Lembaga Bale Literasi, 2025)
This study aims to formulate a conceptual approach to Qur'anic exegesis grounded in the epistemological framework of Ulumul Qur’an. Employing a qualitative method through literature review and conceptual-hermeneutic analysis, the research examines classical and contemporary Ulumul Qur’an texts alongside major tafsir works to evaluate the potential integration between Ulumul Qur’an disciplines and interpretative methodologies. The findings reveal that sciences such as asbabun nuzul (occasions of revelation), makki-madani classification, qira’at (variant readings), nasikh-mansukh (abrogation), and munasabah (intertextual relationships) serve not merely as auxiliary tools but constitute a systematic and relevant methodological framework for interpretation. This study proposes five stages in the conceptual approach: identifying the context of revelation, thematic-conceptual reading, integrating inter-verse relationships, historical verification through nasikh-mansukh analysis, and applying social relevance within contemporary contexts.